SEMIOTIC ANALYSIS OF THE MEANING OF FATHERLESS IN THE LYRICS OF THE SONG “NINA” BY .FEAST - Siti Azzahra Sinaga; Fakhrur Rozi (International Journal of Cultural and Social Science, 2025)
This study aims to examine the representation of the meaning of “fatherless” in the lyrics of the song “Nina” by the Indonesian music group .Feast using Roland Barthes’ semiotic analysis approach. The focus of this study is to identify linguistic and symbolic signs that reflect the experience of losing a father figure, both physically and emotionally. The method used is descriptive qualitative analysis with a three-level semiotic approach: denotation, connotation, and myth. The primary data in the form of the lyrics of the song “Nina” are analyzed based on Barthes’ sign system to reveal the social construction and ideology contained in the musical text. The results of the analysis show that the song lyrics convey the reality of fatherlessness as a complex personal experience and imply a critique of patriarchal norms and modern family structures. These findings enrich the body of cultural communication studies, particularly in understanding how popular music functions as a representational space for sensitive social issues. This study contributes to connecting semiotic studies with contemporary social issues in the context of Indonesian music culture.